Economy And Welfare as Local Government Performance During Election Period - Hurian Kamela; Ryan Saputra Alam; Budi Dharma; Ahmad Rasyiddin; Dediek Tri Kurniawan (Journal of Management and Business Innovations, 2022)
One of study in Public Management was government performance, and this research conduct to measure local government performance especially during the election period. Performance measurement uses a performance score based on Indonesian Ministry of Home Affairs. The aim is to analyze the economy and welfare on performance during the 2016 Mayor/Regent election period. This study used a sample of 174 cities and regencies in Indonesia during the 2016 election period. The research method is regression based on panel data. The dependent variable is Government Performance and independent variables are the economy (GDP) and the population's welfare. The control variables use total assets and legislative measures. The study results are welfare had significant effect on region performance, economy has no effect on performance. These results explain a change in the leader, either the Mayor/Regent, so that performance measurement provides better effectiveness during the election. The research contribution explains that there is an increase in welfare when the election occurs, reinforced by the interest to win the election to create a good image for the Mayor / Regent to be re-elected.Keywords: City, elections, government performance, public management.